Assessing the Quality of Nursing Homes in Managed Care Organizations: Integrating LTSS for Dually Eligible Beneficiaries - Graham, Carrie (Inquiry, 2018)
Little is known about the quality of nursing homes in managed care organizations (MCOs) networks. This study (1) described decision-making criteria for selecting nursing home networks and (2) compared selected quality indicators of network and nonnetwork nursing homes. The sample was 17 MCOs participating in a California demonstration that provided integrated long-term services and supports to dually eligible enrollees in 2017. The findings showed that the MCOs established a broad network of nursing homes, with only limited attention to using quality criteria. Network nursing homes (602) scored significantly lower on 6 selected quality measures than nonnetwork (117) nursing homes. Low registered nurse and total nurse staffing were strong predictors of network nursing homes controlling for facility characteristics. Managed care organizations should consider greater transparency about the quality of their nursing homes and use specific quality criteria to improve the quality of their networks.